Agriculture-nutrition linkages and policies in India - Dev, S. Mahendra (International Food Policy Research Institute, 2012)
By now it is well recognized that agricultural development is important for enhancing nutrition. Agriculture-nutrition linkage has become an emerging area for research and policy in developing countries like India. Earlier studies have shown that there has been a disconnect between agriculture and nutrition particularly regarding policies. In this context, this paper looks at some key entry points for agriculture to influence nutrition and suggests policies for nutrition-sensitive agricultural development, within the current policy framework. In addition, it reviews three key agriculture-food programs for their nutrition sensitivity at the policy level, using a convergence framework. The three key entry points for agriculture-nutrition linkages are inclusive agriculture growth, food prices, and women in agriculture. It provides policy options for strengthening the linkages between agriculture and nutrition. This paper contributes towards an improved policy making in effecting a reduction in malnutrition in India.